Vanet Security and Privacy – An Overview - D, Kumar; V, Sindhu (International Journal of Computer Sciences and Engineering, 2019)
Nearly 1.5 million people die from vehicles accidents per year and nearly 20 million are injured or physically disabled. we can be avoided 60 percent of accidents by using sufficient warnings system. For increasing safety in vehicles, we have Vehicular Ad hoc networks (VANETs) system. This System Designed to increase safety, driving efficiency and make the driving experience more reliable. VANETs connect vehicle into a huge mobile ad hoc network share data on a bigger scale. However, communicating in a free environment makes security and privacy issue an actual challenge, which may disrupt the VANETs system. Researchers have found a resolution to this problem. In this paper, I talked about the different techniques and security parameter which may reflect security and privacy in VANET system.